Structured H∞ Control of an Electric Power Steering System. (25th July 2020) - Zhou, Hongbo; Pang, Aiping; Yang, Jing; He, Zhen
Abstract : Electric power steering (EPS) systems are prone to oscillations because of a very small phase angle margin, so a stable controller is required to increase the stability margin. In addition, the EPS system has parameter disturbances in the gain of the torque map under different conditions, which requires a certain degree of robustness in the control design. This paper synthesizes the multidimensional performance requirements considering the stability margin, robustness, and bandwidth of the system to form an H ∞ optimization matrix with multidimensional performance output in using the structured H ∞ control design. The structured H ∞ controller not only retains the characteristics of traditional H ∞ controllers with excellent robust performance and high stability margin but also has a lower order, which can be better applied in practice. Based on the performance requirements of the system and practical implementation, the structured H ∞ controllers with different orders were designed, and the feasibility of the structured controller was confirmed through comparison and theoretical analysis.